ANALISIS HARAPAN DAN KENYATAAN LAYANAN RAWAT INAP RUMAH SAKIT PENDIDIKAN UNIVERSITAS TANJUNGPURA PONTIANAK - Apriyanto, Dhidik (Program Studi Ilmu Administrasi Bisnis, UPN Veteran Yogyakarta, 2018)
Hospitals as health facilities that provide health services to the community have a very strategic role in accelerating the improvement of public health status. Hospitals are required to provide quality services in accordance with established standards and can be reached throughout the community. This research type is quantitative, using likert scale questionnaire and analyzed using SPSS in placement to 4 quadrant of Cartesian diagram. The results of this study provide that the reality of all services received by inpatients has very satisfied criteria, above 80%. While the diagram analsisi states that the services enter the quadrant I likes speed of service, employees are in place, courtesy service, employees are ready at the table, etc. While in quadrant II are: accurate and accurate doctor diagnosis, good hospital physical form, complete Hospital facilities, etc. Then in quadrant III are: employee's skill in serving, doctor's analysis is undoubtedly, doctor's analysis is not risky, doctor can be trusted, technological means have good, etc. and then the services that included in quadrant IV are: attention of patient satisfaction, suitability of opening and closing schedule, availability of waiting room chair, doctor give info with detail, etc. Keywords: measurement, quality, service, hospital, cartesian diagram.